Bibliometric Computational Mapping Analysis of Publications on Green Finance and Financial Technology Using Vosviewer - Syahwildan, Muhamad; Fajrinur, Muhamad (Proceeding International Pelita Bangsa, 2023)
This study uses a bibliometric method together with computational mapping analysis conducted with VOSviewer to look at the growth of research on green finance and financial technology. The Google Scholar database was used to get article data, which was then entered into the publish or perish reference management program. By using the keywords "Green Financial Technology", "Green Finance", "Financial Technology", and "Green FinTech", article titles and abstracts are utilized to direct the search process. 989 items were discovered and deemed relevant. The research period covered by the study material is the last five years' worth of Google Scholar-indexed publications (2018 to 2022). The study's findings indicate that three terms green finance, financial technology, and fintech—can be used to categorize research on green finance technology. With a strength of 1802 connections, the phrase "Green finance" has 191 links. The terms "Financial technology" and "Fintech" each have 197 and 186 links, respectively, totaling 2046 and 1121 links. The research of the growth of financial technology and green publications over the last five years revealed some noteworthy trends. Between 2018 and 2020, there was a rise from 99 in 2018 to 243 in 2020, however from 2020 to 2022, there was a decline in research. In contrast, 243 investigations on well-known green financial technologies were conducted in 2020. Using VOSviewer, we counted the number of articles that have been written regarding green financial technology and how it relates to green finance. This review may serve as the basis for further investigation into other subjects, such as green fintech.